Measuring the E-learning Readiness Level in Rural Areas During the Covid-19 Pandemic - Kmurawak, Remuz Maurenz Bertho; Mandowen, Samuel Alexander; Beno, Ishak Samuel; Lokollo, Priskila Damaris; Tobing, Helena (Journal of Education Technology, 2022)
Technology plays an important role in life. Information and Communication Technology (ICT) has expanded educational options by enabling teachers and students to use technology to reorganize existing education and training systems. An adequate number of studies have identified the various benefits of implementing e-learning. However, not all institutions that implement online learning get the expected results. In addition, teachers in schools are not homogeneous. This study analyzes e-learning readiness in rural areas during the Covid-19 pandemic. This type of research is descriptive and quantitative. The subjects of this study were ten teachers, three IT staff, two foundation administrators, and 87 students from elementary and junior high schools. Data was collected using questionnaires and interviews. Data were analyzed using Aydin and Tasci's E-Learning Readiness Score, which describes learning outcomes. The results of this study indicate that overall, e-learning is ready to be implemented due to the leadership's commitment in the form of funds and policy support for the implementation of e-learning. Factors that need serious attention are technology infrastructure, human resources, and content.